IMPACT OF CORNEAL CHANGES IN PSEUDOEXFOLIATIVE SYNDROME ON THE COORDINATION DEGREE BETWEEN THE MAKLAKOV TONOMETER AND THE PASCAL DYNAMIC CONTOUR TONOMETER - V. V. Potemkin; E. L. Akopov; E. V. Ageeva (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2017)
Introduction. Pseudoexfoliative syndrome (PEX) changes the morphological structureof corneathat can affects its biomechanical properties. These properties affect the results of the intraocular pressure (IOP) measurement.Purpose of the study isto estimate the effect of PEХ on the error in intraocular pressure measurement (IOP) with Maklakov tonometer in relation to properties of the cornea.Materials and methods. The main group – 126 patients with PEХ, reference group – 104 patients without PEX. The main estimated indicator is the difference between the levels of IOP measured by the Maklakov tonometer and Pascaltonometer and coordination between two methods. Pascal tonometer was used as a reference one.Results and conclusions. The difference between the levels of IOP in the groups was unreliable. When measurements are made with Maklakov tonometer, PEX does not causethe significant tonometry error associated with properties of the cornea.